Some Aspects of the Interpretation of Corpus Delicti of Trading in Influence in the Context of the Principle Nullum Crimen Sine Lege - Mickevičiūtė, Laura (Teisė, 2019)
Taking into consideration the amendments of Article 226 of the Criminal Code of the Republic of Lithuania, the temporal rules of the criminal law, and the content of the principle nullum crimen sine lege (no crime without law), this article assesses the Lithuanian Supreme Court case-law, according to which the provision of the alleged influence feature in Article 226(2) of the Criminal Code of the Republic of Lithuania has only been explained but not given a new feature of the corpus delicti of passive trading influence.
Keywords: the Criminal Code of the Republic of Lithuania; nullum crimen sine lege; trading in influence; the European Court of Human Rights